2017
DOI: 10.1093/europace/eux295
|View full text |Cite
|
Sign up to set email alerts
|

PLAAF score as a novel predictor of long-term outcome after second-generation cryoballoon pulmonary vein isolation

Abstract: PVI using the cryoballoon technique shows acceptable long-term results depending on predictors described by the new PLAAF score, which may facilitate patient selection for PVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
3
24
2
Order By: Relevance
“…In contrast to exclusively CBA studies by Oto et al, Canpolat et al, and Akkaya et al, our study did not show smoking status, AF duration, PeAF, or BMI to be significant predictors of RAF . We also did not find additional components of PLAAF score, such as female gender and variant pulmonary vein anatomy, to be predictors of RAF . Our study did not find additional components of the ALARMEc risk score (mixed CBA and radiofrequency ablation population) including renal insufficiency, metabolic syndrome, and presence of cardiomyopathy to be significant predictors of RAF…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to exclusively CBA studies by Oto et al, Canpolat et al, and Akkaya et al, our study did not show smoking status, AF duration, PeAF, or BMI to be significant predictors of RAF . We also did not find additional components of PLAAF score, such as female gender and variant pulmonary vein anatomy, to be predictors of RAF . Our study did not find additional components of the ALARMEc risk score (mixed CBA and radiofrequency ablation population) including renal insufficiency, metabolic syndrome, and presence of cardiomyopathy to be significant predictors of RAF…”
Section: Discussioncontrasting
confidence: 99%
“…The main findings of our study were that only LAD > 40 mm and ERAF were significant predictors of RAF and that BASEAF2 had the best performance of existing clinical risk scores in predicting RAF. Other studies have consistently shown a large LAD to be a predictor of recurrence following CBA . Similar to our data, other studies have also shown that recurrence of AF in blanking period is a predictor of later recurrence in both PAF and PeAF population .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations